Epigenetic regulation of inflammation in post-operative organ dysfunction: A scoping review protocol - Ruairí Wilson; Charlotte Fern; Carl Goodyear; Ben Shelley (PLoS ONE, 2025)
Introduction The inflammatory response to surgery is complex, dynamic and exhibits variability in magnitude and duration among patients undergoing similar operations. Dysregulated inflammation is associated with post-operative complications such as organ dysfunction, particularly after major surgery. Epigenetic modifications enhance (or suppress) selective gene transcription without altering DNA sequences, effectively regulating gene expression. Several studies have investigated epigenetic regulation of the immune system in the context of surgery, often studying organ-specific dysfunction. Objectives We propose a novel scoping review protocol to collate and synthesise existing studies investigating epigenetic regulation of post-operative inflammation, as a key mechanism of post-operative organ dysfunction and complications. We will map knowledge gaps to inform future research in this emerging field. Methods and analysis This scoping review protocol has been created following the Joanna Brigg’s Institute (JBI) updated guidelines for conducting scoping reviews. The protocol has been further examined alongside the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) extension for Scoping Reviews (PRISMA-ScR) checklist and is registered on Open Science Framework (doi.org/10.17605/OSF.IO/CE8FB). Published human studies from 1946 to the present will be considered. Studies will include patients undergoing surgery, where epigenetic regulation of the immune system is investigated alongside assessment of organ dysfunction or complications. Searches will be conducted using Medline (via OVID) and Embase. Two reviewers will independently screen titles, abstracts and full texts of studies meeting the inclusion criteria. Following study screening, a customised data extraction form will collect study information related to the review questions and inclusion criteria (population, concept, context). Results will be presented by diagrammatic mapping of studies and tabular representation of findings.